Teacher's Strategy in Forming Elementary Student Character - Fauji Koda; Taufik Abdullah (Universitas Negeri Semarang, 2023)
Character education is not just educating about what is good and what is not good, but also to get used to all the good things that they can apply in their daily lives and can implement them consciously. This study aims to describe the teacher's strategy in the formation of student character in Elementary School 25 City of Ternate in implementing the teacher's strategy in forming the character of student discipline in Public Elementary School 25 City of Ternate. This research is a qualitative descriptive study. Data collection techniques with interviews, observation, and documentation. test the validity of the data by triangulation of sources and techniques. The data in the analysis of the results of this study are: (1) teacher's strategy in the formation of students' disciplinary character. Character education is to develop the potential of students to become human beings who have faith and are devoted to God Almighty, have noble character, are healthy, knowledgeable, capable, creative, independent. The teacher is a figure whose every move is modeled by his students. To become a teacher is not an easy thing that can be done by everyone because it requires special skills. someone who teaches science. professional education with the main task of educating, teaching, guiding, directing, training, assessing, and evaluating students